2016
DOI: 10.29252/arakmu.10.6.45
|View full text |Cite
|
Sign up to set email alerts
|

Foodborne Botulism: A Study of 57 Cases in Northwest Iran

Abstract: Background: Foodborne botulism (FBB) is a rare paralyzing disease caused by ingestion of foods contaminated with botulinum neurotoxin (BoNT). It is still a health concern in many countries. This study aimed to investigate the epidemiology of FBB in West Azerbaijan Province, Iran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…This finding is in line with other cases reported in the united states, San Francisco (19) and Atlanta, Georgia (20) especially in patients who were poisoned with BoNT type A or B. It is important to differentiate botulism and other central nervous system deficits which may mimic botulism such as Guillain-Barre syndrome, Myasthenia Gravis and Lambert-Eaton myasthenic syndrome (3,9). These patients usually have fever, ataxia and elevated cerebrospinal fluid (CSF) protein, but they often have normal pupils (18,21).…”
Section: Discussionsupporting
confidence: 88%
“…This finding is in line with other cases reported in the united states, San Francisco (19) and Atlanta, Georgia (20) especially in patients who were poisoned with BoNT type A or B. It is important to differentiate botulism and other central nervous system deficits which may mimic botulism such as Guillain-Barre syndrome, Myasthenia Gravis and Lambert-Eaton myasthenic syndrome (3,9). These patients usually have fever, ataxia and elevated cerebrospinal fluid (CSF) protein, but they often have normal pupils (18,21).…”
Section: Discussionsupporting
confidence: 88%
“…In previous reviews conducted in Iran, the number of men with botulism was reported higher than women, and their mean age was 22.35 years [16]. Also, in previous studies in Iran, locally produced cheese was the most common food causing botulism, and neurotoxin type A was the highest neurotoxin found in patients [16,17]. Also, in our review, the mean age of the patients was 36.9 years, the number of men was higher than that of women, and dairy products followed by canned foods were the most consumed foods.…”
Section: Discussionmentioning
confidence: 94%